The pesticide picloram affects biomembrane models made with Langmuir monolayers - Lemma, Tibebe [UNESP]; Marques Ruiz, Gilia Cristine [UNESP]; Oliveira, Osvaldo N.; Constantino, Carlos J.L. [UNESP] (Elsevier, 2019)
Cell membrane models are useful to obtain molecular-level information on the interaction of biologically-relevant molecules such as pesticides whose activity is believed to depend on its effects on the membrane. In this study, we investigated the interaction between the widely used pesticide picloram with Langmuir monolayers of binary and ternary mixtures comprising 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), sphingomyelin (SM) and cholesterol (Chol), which could be taken as representative of ocular membranes in humans. Picloram expanded the molecular area of DOPC/SM and DOPC/SM/Chol monolayers as the pesticide penetrated the hydrophobic region of the mixtures. A clear correlation was also found between the compressibility modulus (Cs−1) and the presence of cholesterol in the ternary monolayer. Data from polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS) confirmed that picloram interacts with both the acyl chains and headgroups. Spectral shifts and band broadening were induced by picloram, particularly for the phosphate and choline groups, probably owing to its H-bonding ability. The effects reported here on the lipid monolayers may be evidence of the possible activity of picloram on mammalian cell membranes, which highlights the importance of strict control of the level of exposure of humans dealing with pesticides.
Keywords: DOPC/SM; DOPC/SM/Chol; GUV; Monolayer; Picloram; π-A isotherm